PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BERT LIGHTING ASIA JAKARTA SELATAN - Mishel Alilah Gunawan; Dewi Lestari (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of training and work discipline on employee performance, both partially and simultaneously. The study uses a quantitative research method involving employees as samples. The sample used is a saturated sample with a total of 60 people. The research employs various tests including validity tests, reliability tests, classical assumption tests, correlation coefficient tests, regression coefficient tests, coefficient of determination tests, and hypothesis tests. The results of the study obtained the multiple regression equation Y = 11.184 + 0.263X1 + 0.483X2 + 4.700. The regression coefficient value for the performance variable is 11.184, which concludes that if training (X1) and work discipline (X2) remain constant (unchanged), the consistency value of performance (Y) will be 11.184. The t-test result for Training on Performance is 2.777 > 2.002 with a significance of 0.007 > 0.05, thus H0 is rejected and Ha is accepted, indicating a positive and significant effect of training on employee performance. Meanwhile, the t-test result for Work Discipline on Performance is 5.432 > 2.002 with a significance of 0.000 < 0.05, thus Ha is accepted and H0 is rejected, indicating a positive and significant effect of work discipline on employee performance. Additionally, the F-test result for Training and Work Discipline on Performance is 19.751 > 3.160 with a significance level of 0.05, yielding a significance value of 0.000 < 0.05. This means that the hypothesis stating that training and work discipline simultaneously affect employee performance is accepted.